Study of Response Analysis of Youth Unemployment Rate in Economy Globalization In Asean - Riniati M P; Duwi Yunitasari; Desy Arishanti (Trunojoyo University of Madura, 2022)
Unemployment is a variable of concern to many countries. The unemployment rate has a negative nature on economic growth in a country. So that various policies were formed in an effort to minimize the increase in the number of unemployed. This study focuses on the Youth Unemployment Response to economic globalization in ASEAN by using secondary time series data from 2010 to 2019.In this study, it was found that the economic globalization aspect gave rise to several different responses to Youth Unemployment in ASEAN. Changes in trade globalization for the period one to ten gave rise to a positive response, while in the aspect of financial globalization it was responded negatively by the youth unemployment rate. In the aspect of youth unemployment responsiveness, the variables of financial and trade globalization have contributed greatly to the increase in the number of youth unemployed in ASEAN. This can be a recommendation for the government, especially Indonesia, in boosting young unemployed people to stay in a safe position. But on the other hand, it does not rule out the flow of economy globalization.